Teaching Machines: The History of Personalized Learning, 2021. - Irina Tursunkulova (The Canadian Network for Innovation in Education (CNIE), 2022)
Teaching Machines by journalist Audrey Watters blends the historical and political events of 1920-1960s in the United States and the changes in the K-12 school system, chronicling the rapid development of educational technology markets to show the inception and evolution of teaching machines. The author expresses her indignance towards Silicon Valley entrepreneurs who continue launching educational businesses, under the assumption that their "new" technological breakthrough will change the "stagnant" field of education technology. This book explicates how the "new idea" of personalized learning offered by current educational technology companies and industries dates back a century to the 1920s.